PENGARUH PERTUMBUHAN PENJUALAN DAN KEBIJAKAN HUTANG TERHADAP HARGA SAHAM PADAPERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siska Oktavia; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the Effect of Sales Growth and Debt Policy on Stock Prices. Where the independent variable in this study is Sales Growth and Debt Policy and the dependent variable is the Stock Price. This study uses secondary data in the form of company financial reports and annual reports on annual reports of Food and Beverage companies listed on the IDX. Sampling using purposive sampling technique, which is used is 8 companies. Data analysis using simple linear regression analysis, multiple linear regression analysis, T test, F test and test coefficient of determination using SPSS 16 devices. The results of the analysis show that the sales growth variable partially (t test) influences the stock price of food and beverage companies listed in Indonesian Stock Exchange, the variable debt policy partially (t test) does not affect the stock price of food and beverage companies listed in Indonesian Stock Exchange . The simultaneous test results (f test) show no influence from the sales growth variable and debt policy on stock prices in food and beverage companies listed in Indonesian Stock Exchange. Keywords: Sales Growth, Debt Policy, Stock Prices